Inovasi Pembelajaran Matematika SD/MI dengan Pendekatan Matematika Realistik - Lisa (PGMI IAIN Lhokseumawe, 2022)
One of the innovations for learning mathematics in SD/MI is the realistic mathematics approach. The characteristics of Mathematics Learning in SD/MI are: a) Mathematics learning uses the spiral method, b) Gradual mathematics learning, c) Mathematics learning uses an inductive method, d) Mathematics learning adheres to the truth of consistency, e) Mathematics learning should be meaningful, namely the way of teaching material learning that prioritizes understanding rather than memorization. Fun math learning. Fun math learning helps students to like math more. Mathematics is known as a complicated and difficult subject that has made many people dislike mathematics. Realistic Approach is an approach to the learning process that starts from things that are real for students (reality), and emphasizes 'process of doing mathematics' skills with the characteristics of using contextual problems, using models, using student contributions and productions, being interactive, and intertwining